Hubungan Beban Kerja Dan Stres Kerja Dengan Kinerja Perawat RSUD La Patarai Kabupaten Barru - Putri Aqilla Herman; Nurbaeti; Andi Sani (Window of Public Health Journal, 2026)
Nurse performance refers to the duties, authorities, and responsibilities nurses carry out to the best of their ability to achieve professional goals and unit targets. Based on the results of a survey by the Indonesian National Nurses Association (PPNI) in 2020, approximately 50.9% of nurses working in Indonesia experience work stress and experience the impact of physical workload, such as frequent dizziness, neck pain, and fatigue due to lack of sleep, due to excessive workload, and taking up time to rest. The purpose of this study was to determine the relationship between workload and work stress and nurses' performance at La Patarai Regional Hospital, Barru Regency. Data were analyzed using the chi-square test at a 95% confidence level (α = 0.05). The results showed that there was a significant relationship between workload variables and nurse performance (p = 0.015), stress variables based on psychological aspects also showed that there was a relationship between work stress and nurse performance (p = 0.003), and work stress variables based on physiological aspects also showed that there was a relationship between work stress and nurse performance (p = 0.019). These results confirm that high workloads and job stress will impact nurse performance. Hospital management is advised to manage workloads in a balanced manner and provide adequate support, both of which are crucial for maintaining and improving nurse performance.